2017
DOI: 10.1002/ajoc.201700340
|View full text |Cite
|
Sign up to set email alerts
|

Paal–Knorr Furan Synthesis Using TiCl4 as Dehydrating Agent: A Concise Furan Synthesis from α‐Haloketones and β‐Dicarbonyl Compounds

Abstract: An efficient andf acile methodf or the Paal-Knorr furan synthesis using titaniumt etrachloride as dehydrating agenti sd escribed. Tricarbonyl compounds, prepared through the nucleophilic substitution of a-halogenated ketones and b-dicarbonyl compounds, are easily condensed to their corresponding polysubstituted furans. The reaction also occurs efficiently with tetracarbonyl compounds derived by dimerization of b-dicarbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…2-Methyl-1,5,6,7-tetrahydro-4H-indol-4-one (3b). 28 Prepared according to procedure A using (S)-2-aminopropan-1-ol (37 mg, 0.50 mmol) and 1,3-cyclohexanedione (56 mg, 0.50 mmol), and the residue was purified by 100−200 mesh silica gel column chromatography (EtOAc/hexane = 45:65) to afford 2-methyl-1,5,6,7-tetrahydro-4Hindol-4-one 3b (56 mg, 76%) as a dark brown solid. Melting point: 115−120 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2-Methyl-1,5,6,7-tetrahydro-4H-indol-4-one (3b). 28 Prepared according to procedure A using (S)-2-aminopropan-1-ol (37 mg, 0.50 mmol) and 1,3-cyclohexanedione (56 mg, 0.50 mmol), and the residue was purified by 100−200 mesh silica gel column chromatography (EtOAc/hexane = 45:65) to afford 2-methyl-1,5,6,7-tetrahydro-4Hindol-4-one 3b (56 mg, 76%) as a dark brown solid. Melting point: 115−120 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It is reported that azepinium ions can be generated by the ether cleavage reaction of 2-methoxy-2 H -azepine derivatives with titanium tetrachloride as a Lewis acid [23,24]. Furthermore, titanium tetrachloride is also a powerful dehydrating agent and demonstrates a prominent effect in the condensation reaction of triketones to yield furans [25]. Apart from the reaction paths reported in the literature (Scheme 1a,b) [22], another reaction route for the one-pot synthesis of benzofuran was proposed in Scheme 3 [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Furans are one type of important compound among the fivemember heterocyclic compounds. They have been broadly examined because of their activity and application in a large number of pharmaceuticals [1] and functional materials. Substituted furan compounds show typical biomedical activities like antimicrobial, [2] antihypoglycemic, [3] anti-inflammatory, [4] anti-cancer, [5] anti-depressant, [6] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[10b] Stetter reaction is a well-known method because of its versatility in the synthesis of 1,4-dicarbonyl compounds, [11] which involves the reaction of an enone with an aldehyde in the presence of a base and a thiazolium salt as the catalyst. [12] For years, the Paal-Knorr method has been widely reported for the synthesis of substituted furan compounds by different researchers using either protonic acid or Lewis acid as the catalyst/reagent, some typical examples are summarized in Figure 1: (a) reductive ring-closure of but-2-ene-1,4-diones/but-2-yne-1,4-diones into furans using formic acid as the reducing reagent in the presence of a catalytic amount of palladium on carbon and in poly(ethylene glycol)-200 (PEG 200) medium under microwave irradiation; [13] (b) cyclization of 2,5-diketoesters catalysed by sulphuric acid (H 2 SO 4 ) in benzene; [14] (c) heating 1,4-dicarbonyl ester under microwave irradiation in ethanol solution using hydrochloric acid (HCl) as the catalyst; [15] (d) condensation of 1,4-diketones into furans upon treatment with catalytic p-toluenesulfonic acid (p-TsOH) in refluxing toluene; [16] (e) reduction of 2-(methylthio)-1,4-diaryl-2-butene-1,4-dione with stannous chloride in the presence of concentrated HCl and acetic acid (CH 3 COOH) at reflux; [17] (f) condensation of tricarbonyl compound by using titanium tetrachloride as dehydrating reagent in toluene; [1] (g) reductive ring-closure of 2-ene-1,4-dione into furans by diphosphorus tetraiodide in chloroform. [18] Nevertheless, there are some drawbacks to the above-mentioned synthetic methods.…”
Section: Introductionmentioning
confidence: 99%